Hydrogen production from crude oil with fine iron particles through microwave-initiated catalytic dehydrogenation promoted by emulsified feed. (27th December 2018) - Yan, Yuqiang; Gonzalez-Cortes, Sergio; AlMegren, Hamid; Edwards, Peter P.; Cao, Fahai; Xiao, Tiancun
Abstract: With increasing concerns about climate change caused by carbon dioxide emissions, decarbonization is rapidly becoming an important and attractive challenge for continuing fossil fuel utilization. This paper reports an entirely new route of producing hydrogen directly from crude oil through microwave-initiated, iron-catalyzed deep dehydrogenation. Importantly, there is very little carbon dioxide emission in this process, a key element towards stabilising global mean temperature. The analytical techniques of Scanning Electron Microscope, Transmission Electron Microscopy, Temperature Programmed Oxidation and Raman spectroscopy were employed to interrogate the catalytic process and the nature of carbon deposition over the catalyst which was brought about by the dehydrogenation process. The presence of emulsified feed significantly promotes hydrogen production, owing to its presence depressing carbonaceous deposition on the catalyst together with the occurrence of the micro-explosion phenomenon. Graphical abstract: Highlights: H2 were rapidly produced through microwave-initiated dehydrogenation of crude oil. There was nearly no carbon dioxide emission in this process. Emulsifying the crude oil feed significantly promotes hydrogen production.